The Role Of Malaysian And Indonesian Ulama In Hadith Studies: Muhammad Idris Al-marbawi And T.m. Hasbi Ash Shiddieqy - Ramli Abdul Wahid; A. Irwan Santeri Doll Kawaid (Universitas Islam Negeri, Sumatera Utara Medan, 2024)
Non-Indexed Publication